Aux marges de l'emploi: parcours de travailleuses domestiques québécoises, 1950-2000 - Charron, Catherine (Les éditions du remue-ménage, 2018)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques; travail; travail domestique

Du commerce des fourrures au libre-échange: la foresterie et les femmes des Premières nations au Canada - Rude, Darlene; Deiter, Constance; Canada Condition féminine Canada Recherche en matière de politiques (Condition féminine Canada, 2004)
Le présent rapport alimente la discussion sur les femmes et les accords commerciaux, en établissant un lien entre les femmes des Premières nations, la foresterie et le libre-échange. Il comprend une étude documentaire qui aborde les domaines suivants : les rapports sociaux entre les sexes et les femmes autochtones, les rôles traditionnels, le commerce des fourrures, le titre aborigène et les droits ancestraux, et le libre-échange et l’exploitation forestière dans les collectivités des Premières nations.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; commerce; commerce de peaux; cours; discipline; environnement; femmes* autochtones; histoire; histoire et politique; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques; travail

America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Haymarket series, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis

Le Bordel: Milieu De Travail Contrôlé - Lévesque, Andrée (Labour / Le Travail, 1987)
PENDANT LONGTEMPS, des milliers de femmes gagnèrent leur vie dans des bordels à Montréal. L'étude de leur milieu de travail pendant les années vingt et trente révèle une organisation hiérarchique et des conditions dont le contrôle échappait aux principales intéressées. L'appareil judiciaire et policier, les organisations de réformes sociales, le clergé et les médecins hygiénistes affectaient, par la tolérance ou la répression, le cadre dans lequel s'exerçait la prostitution. Plus directement, les souteneurs, les tenancières et leurs gérantes déterminaient les conditions quotidiennes de travail. Les changements observés pendant toute cette période sont plus imputables à la vigilance policière qu'aux fluctuations économiques ou aux efforts des travailleuses elles-mêmes.
Keywords: 1900-1999; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; montréal; premier cycle; prostitution; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; thématiques; travail; travail du sexe; travail du sexe-prostitution

Cheap amusements: Working women and leisure in turn-of-the-century New York - Peiss, Kathy Lee (Temple University Press, 1986)
Contenu: The Homosocial World of Working-Class Amusements -- Leisure and Labor -- Putting on Style -- Dance Madness -- The Coney Island Excursion -- Cheap Theater and the Nickel Dumps -- Reforming Working Women's Recreation.
Keywords: 1800-1899; 1900-1999; approches et analyses; cours; discipline; his4443; histoire; histoire des femmes*; histoire et politique; loisirs des femmes*; new york; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sociologie; thématiques; travail; travail des femmes*